Power line compensation study of a static synchronous series compensator (SSSC) based on soft switching 48-pulse PWM inverter - Ustun, Taha Selim; Mekhilef, Saad (American-Eurasian Network for Scientific Information, Jordan, 2009)
This paper discusses a Static Synchronous Series Compensator which is constructed with a 48-pulse inverter. Extensive simulation studies are carried out to verify the proper operation of the mentioned Flexible AC Transmission Systems (FACTS) device. In MATLAB simulation environment the designed device is connected to a power system that is comprised of three phase power source, transmission line, line inductance and load. The system parameters such as line voltage, line current, reactive power Q and real power P transmissions are observed both when the Static Synchronous Series Compensator is connected to and disconnected from the power system. The compensation achieved by the SSSC and its effects on the line voltage, line current, phase angle and real/reactive power flow are examined in detail. The motivation of modeling a Static Synchronous Series Compensator from a multi-pulse inverter is to enhance the voltage waveform of the device and this is observed in total harmonic distortion (THD) analysis performed in the end. The results of the study shows that the voltage injection is successfully achieved by the new device and the power flow and phase angle can be controlled. Also the THD analysis assures that this is accomplished without comprising from the quality of the line voltage and current.